2017
DOI: 10.1002/csr.1466
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Normative CSR‐Promoting Institutions in Stimulating CSR Disclosures in Developing Countries

Abstract: This paper provides evidence that CSR (corporate social responsibility) forums and networks such as the United Nations Global Compact Local Network (UNGC), non-governmental organizations (NGOs) such as the World Wide Fund (WWF) for Nature, and CSR standards such as International Organization for Standardization (ISO) 14000 play a significant role in driving CSR disclosure, using data from publicly quoted companies in Pakistan. The role of CSR-promoting institutions in enhancing capacity can provide a key expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 140 publications
(190 reference statements)
1
70
0
2
Order By: Relevance
“…Existing research has also found that directors Third, scholars have focused on the impact of industry factors on CSR performance. The prior studies suggest that effective industry self-regulatory organizations and nongovernmental organizations (NGOs) that promote CSR play a pivotal role in making CSR progress (Ali & Frynas, 2018;Campbell, 2007;Marquis et al, 2007). The CSR initiatives of leading companies and competitors in one industry will inspire firms to take similar social responsibility measures to acquire legitimacy and survival in society, and the type of industry determines that enterprises focus on different aspects of social responsibility (Matten & Moon, 2004; Amor-Esteban, Galindo-Villardón, & García-Sánchez, 2019).…”
Section: Determinants Of Csrmentioning
confidence: 99%
“…Existing research has also found that directors Third, scholars have focused on the impact of industry factors on CSR performance. The prior studies suggest that effective industry self-regulatory organizations and nongovernmental organizations (NGOs) that promote CSR play a pivotal role in making CSR progress (Ali & Frynas, 2018;Campbell, 2007;Marquis et al, 2007). The CSR initiatives of leading companies and competitors in one industry will inspire firms to take similar social responsibility measures to acquire legitimacy and survival in society, and the type of industry determines that enterprises focus on different aspects of social responsibility (Matten & Moon, 2004; Amor-Esteban, Galindo-Villardón, & García-Sánchez, 2019).…”
Section: Determinants Of Csrmentioning
confidence: 99%
“…The Act came into effect on April 1, 2014 (Chatterjee & Mitra, ; Khandelwal & Bakshi, ; Pandey & Pattnaik, ; Pattnaik & Shukla, ; Sarkar & Sarkar, ; Sharma, ). It has been observed that after the CSR mandate, the scale of projects in India has broadened while the number of projects has reduced, which reflect companies' strategic focus to implement projects that bring substantial change in the society (Ali & Frynas, ; Chatterjee & Mitra, ; Sarkar & Sarkar, ). The authors contend that this focus was the primary objective of introducing changes in the Companies Act.…”
Section: Csr In Indiamentioning
confidence: 99%
“…Nevertheless, regarding the UNGC, the research so far has identified many problems, in particular, substantial cross-country differences in adoption and disclosure levels (Ali and Frynas 2018;Schembera 2018;Lim 2017); insufficient quality of annual Communications on Progress (COPs), the primary tool for monitoring participants' commitment to the UNGC Ten Principles (Coulmont et al 2017;Zilic et al 2019); as well as numerous cases of companies adhering to the Principles for the instrumental reasons of seeking protection from criticism and improving their reputation rather than having real intentions of applying them in their everyday operations (Amer 2018;Wettstein et al 2019). Moreover, studies on the practical impacts of the UNGC on the business operations and risk management of companies are almost non-existent (cf.…”
Section: Literature Review and The Rationale Of The Studymentioning
confidence: 99%
“…However, despite the prominent position of the UNGC within the contemporary global governance architecture, there are serious doubts about its actual impacts in the contemporary scholarly literature (cf. Ali and Frynas 2018;Schembera 2018;Lim 2017;Coulmont et al 2017;Zilic et al 2019). The criticism points especially to the lack of intergovernmental legitimacy, the absence of oversight by the UN General Assembly and the blue-wash phenomenon, i.e., participation to acquire public legitimacy without any real intention to adhere to the Ten Principles of the UN Global Compact.…”
Section: Introductionmentioning
confidence: 99%